Early intraocular pressure changes following different keratoplasty techniques and association with cornea parameters and anterior chamber depth. - Gumus, Gulsah; Altan, Cigdem; Yildirim, Yusuf; Beşek, Nilay Kandemir; Genç, Selim; Kirgiz, Ahmet; Durusoy, Gonul Karatas; Ağca, Alper (Therapeutic Advances in Ophthalmology)
Background: Corneal transplantation surgery is associated with an increased risk of intraocular pressure (IOP) elevation. Increased IOP may cause irreversible vision loss and graft failure. Objective: We aimed to evaluate early IOP changes following different keratoplasty techniques and to investigate the relationship between corneal thickness (CT), keratometry values, anterior chamber depth (ACD), and IOP changes. Methods: We included patients who underwent penetrating keratoplasty (PK), deep anterior lamellar keratoplasty (DALK), and Descemet membrane endothelial keratoplasty (DMEK) in this observational study. ACD, CT, and keratometry measurements were repeated postoperatively at hour 24, week 1, and month 1. IOP measurements were repeated at postoperative hours 6 and 24, week 1, and month 1 by Tono-Pen XL. Results: In total, 22 patients underwent PK, 12 patients underwent DALK, and 19 patients underwent DMEK. The difference between the IOP preoperatively and postoperatively hour 6, and between the IOP preoperatively and postoperatively hour 24 was statistically significant in the three types of surgery (p < 0.05 for each). The difference between preoperative and postoperative week 1 IOP was statistically significant only in the PK group (p = 0.023). When the IOP was compared between the three types of surgeries, the IOP at postoperative week 1 in the PK group was significantly higher than the DALK and DMEK groups (p = 0.021). There was no correlation between ACD, CT, K values, and IOP in any group. Conclusion: IOP may increase in all types of keratoplasty during the first hours after surgery, but PK has a risk of high IOP longer in the early postoperative period. PK patients should be followed more carefully during postoperative week 1 to check for an increase in IOP.